Pengaruh Loneliness terhadap Subjective Well-Being pada Mahasiswa Rantau - Bella Azahra Putri Maulana; Hatta, Muhammad Ilmi (Bandung Conference Series: Psychology Science, 2024)
Abstract. Overseas students often face various challenges, including psychosocial stress, differences in social support received, and other interpersonal and intrapersonal problems that arise as a consequence of the adaptation process to a new social and cultural environment. Overseas students who experience difficulties in building and maintaining meaningful social relationships in a new environment, can trigger feelings of loneliness that have the potential to affect their subjective well-being. This study aims to determine the effect of loneliness on subjective well-being in overseas students at the Bandung Islamic University (Universitas Islam Bandung). Using a quantitative approach with a causality design, the study involved 362 participants (132 males, 230 females). The measuring instrument used for the loneliness variable is the Loneliness Scale Version 3 (R-UCLA Version 3) which has been modified by Anggraeni (2018), while for the subjective well-being variable using the Satisfaction with Life Scale (SWLS) and the Positive and Negative Experience Scale (SPANE) which has been adapted by Akhtar (2019). Multiple linear regression analysis was employed to evaluate the influence of personality, social desirability, and depression aspects of loneliness on subjective well-being. Results indicate that loneliness negatively affects subjective well-being, accounting for 48.1% of the variance. The depression aspect showed the strongest influence (30.2%), followed by personality (10.9%), and social desirability (7%). Abstrak. Mahasiswa rantau sering kali menghadapi berbagai tantangan, termasuk stres psikososial, perbedaan social support yang diterima, serta masalah interpersonal dan intrapersonal lainnya yang muncul sebagai konsekuensi dari proses adaptasi terhadap lingkungan sosial dan budaya yang baru. Mahasiswa rantau yang mengalami kesulitan dalam membangun dan mempertahankan hubungan sosial yang bermakna di lingkungan baru, dapat memicu perasaan kesepian yang berpotensi mempengaruhi subjective well-being mereka. Penelitian ini bertujuan untuk mengetahui pengaruh loneliness terhadap subjective well-being pada mahasiswa rantau di Universitas Islam Bandung. Metode penelitian yang digunakan adalah kuantitatif dengan desain penelitian kausalitas. Penelitian ini melibatkan 362 mahasiswa rantau di Universitas Islam Bandung, dengan keterangan 132 responden laki-laki dan 230 responden perempuan. Alat ukur yang digunakan untuk variabel loneliness adalah Loneliness Scale Version 3 (R-UCLA Version 3) yang telah dimodifikasi oleh Anggraeni (2018), sedangkan untuk variabel subjective well-being menggunakan alat ukur Satisfaction with Life Scale (SWLS) dan Scale Positive and Negative Experience (SPANE) yang telah diadaptasi oleh Akhtar (2019). Teknik analisis data menggunakan regresi liniear berganda untuk mengukur pengaruh personality, social desirability, dan depression pada variabel loneliness terhadap subjective well-being. Hasil penelitian menunjukkan bahwa loneliness berpengaruh negatif terhadap subjective well-being dengan kontribusi sebesar 48.1%, yaitu dengan keterangan aspek depression memiliki pengaruh terbesar (30.2%), diikuti personality (10.9%), dan social desirability (7%).